The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/carcin/bgi103
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen resistance and Her2/neu expression in an aged, irradiated rat breast carcinoma model

Abstract: Clear links have been established between occupational or therapeutic radiation exposure and breast cancer. Tamoxifen chemoprevention following radiation exposure may be able to reduce the risk of developing breast cancer later in life. In order to model carcinogenesis in this setting, an in vivo model of tamoxifen chemoprevention and tamoxifen failure in a radiation-induced rat mammary carcinoma model was characterized. Two hundred twenty-seven 60 day old female rats received whole body or sham exposure to io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…5), as was previously reported (5,6,30). Although tamoxifen has been shown previously to decrease body mass significantly in rats (31,35), the absolute difference in body weight did not achieve statistical significance at any time. However, the growth rate of rats during treatment with tamoxifen (0.09 g/day) was significantly slower than the rate in the control group (0.455 g/day) p<0.04.…”
Section: Resultssupporting
confidence: 75%
“…5), as was previously reported (5,6,30). Although tamoxifen has been shown previously to decrease body mass significantly in rats (31,35), the absolute difference in body weight did not achieve statistical significance at any time. However, the growth rate of rats during treatment with tamoxifen (0.09 g/day) was significantly slower than the rate in the control group (0.455 g/day) p<0.04.…”
Section: Resultssupporting
confidence: 75%
“…Rat mammary carcinomas exhibit a hormone dependency that is similar to that of human breast cancer. It has been reported that long-term tamoxifen treatment reduces the incidence of radiation-induced mammary cancer in rats 47 , suggesting that the hormonal environment greatly influences radiation-related mammary cancer risk. In the present study, the pre-pubertal exposure resulted in premature cessation of regular estrous cycling, like that observed for young female patients who received radiation therapy and experienced premature menopause 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after excision, the left femur from each mouse was fixed in 10% neutral buffered formalin for histopathological analysis using well-established methods (25, 26). Briefly, formalin-fixed femurs were demineralized in formic acid solution, washed, processed in an automated processor, embedded in paraffin, sectioned at 5 µm, mounted on glass microscope slides, and stained with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%